Social justice in consumer protection: the Indonesian framework = (Keadilan sosial dalam perlindungan pengguna: rangka kerja Indonesia) - Jessica Los Banos; Gwendolyn Ingrid Utama (Penerbit UKM, 2013)
The legal system of Indonesia is underpinned by the Pancasila, a political philosophy introduced by President Sukarnowhen Indonesia obtained independence from the Dutch in 1945. Its fifth pillar, the ‘Keadilan Sosial bagi Seluruh RakyatIndonesia’ which is literally translated as “social justice for the whole people of Indonesia”, calls for the equitableallocation of resources while protecting the weaker sector of the Indonesian population. Adopting a substantive-proceduraldichotomy approach, this paper examines how this indigenous conception of social justice has shaped and in fluenced consumer protection in Indonesia. It explores specific aspects of social justice in the formulation of consumer rightsand obligations, representation, education and dispute settlement, particularly in the establishment of the National Consumer Protection Agency (NCPA) and the Consumer Dispute Settlement Board (CDSB). As expected, the paper finds evidence that the Pancasilan notion of social justice advances a liberal consumer protection framework as embodied in Indonesia’s Law on Consumer Protection (LCP), which while balancing substantive rights procedurally tilts the regimein favour of consumers to temper the stronger position of entrepreneurs. It also predictably con firms that consistent withsocial justice tenets, consumer protection in Indonesia is pro-consumer and encourages shared responsibility betweenthe government and the private secto